Implementasi Problem Base Learning untuk Pemahaman Konsep Fact Finding dalam Analisis & Desain Sistem Informasi - Oslan, Yetli; Kristanto, Harianto (Proceedings of KNASTIK, 2012)
Fact finding is a difficult task and need a long time. This process can be disrupted alsoby personal perception researchers. For information systems workers, fact-finding isone of the main tasks in performing the steps of analysis and design of informationsystems. Therefore, the discovery of the facts is a competence that need to be owned bya student who will be working at information systems environment. The learningmethod uses Problem Based Learning (PBL) is a learning method for understandingthe concept of Fact Finding uses Ishikawa diagrams and Pareto analysis. Studentstargeted has ability to level the synthesis of Fact Finding, which is able to apply indifferent cases, especially in information systems projects.